2019
DOI: 10.3390/medicina55090577
|View full text |Cite
|
Sign up to set email alerts
|

Tri-Ponderal Mass Index: A Screening Tool for Risk of Central Fat Accumulation in Brazilian Preschool Children

Abstract: Background and Objectives: To verify the use of the tri-ponderalmass index (TMI) as a screening tool for risk of central fat accumulation in preschool children. Materials and Methods: An observational, analytical study was carried out on samples from children 2 to 5 years of age. The body mass index (BMI) and the tri-ponderalmass index (TMI: Weight/height3) were calculated. The waist circumference-to-height ratio (WHtR) was used to classify central fat accumulation risk. Preschoolers whose WHtRwas in the upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
10
1
1
Order By: Relevance
“…It has been shown that percent of body fat (BF%) as a gold standard was better predicted by TMI than by BMI ( 10 , 25 ), although one study reported that both relative fat mass pediatric (RFMp) based on height and waist circumference [WC], and waist-to-height ratio (WHtR) performed better than both TMI and BMI ( 25 ). When WHtR was used to define central obesity as the gold standard, three articles showed that TMI was better than BMI correlated with central fat accumulation in both preschool-aged children aged 2–5 years ( 24 ) and children and adolescents aged 5–17 years ( 19 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that percent of body fat (BF%) as a gold standard was better predicted by TMI than by BMI ( 10 , 25 ), although one study reported that both relative fat mass pediatric (RFMp) based on height and waist circumference [WC], and waist-to-height ratio (WHtR) performed better than both TMI and BMI ( 25 ). When WHtR was used to define central obesity as the gold standard, three articles showed that TMI was better than BMI correlated with central fat accumulation in both preschool-aged children aged 2–5 years ( 24 ) and children and adolescents aged 5–17 years ( 19 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 describes the characteristics of the included studies including 14 for the association between TMI and body fat in childhood and adolescence (10,14,(18)(19)(20)(21)(22)(23)(24)(25)(26)(41)(42)(43), 20 for TMI and CVRFs in childhood and adolescence (13-18, 21, 26-34, 42-45), and 4 for the association in adulthood (35)(36)(37)46). Twentyfive of the included studies used a cross-sectional design (10, 13, 15-28, 30-34, 41-43, 45), 2 a retrospective design (14,44), 1 a case-control design (29), and 4 a cohort design (35)(36)(37)46).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Również Nascimento i wsp. [61] po przebadaniu brazylijskich dzieci w wieku przedszkolnym uznali, że TMI jest narzędziem, przewyższającym BMI, w ocenie ryzyka centralnego gromadzenia tłuszczu oraz wczesnej identyfikacji dzieci z możliwym ryzykiem chorób sercowo-naczyniowych i przewlekłych chorób niezakaźnych.…”
Section: Tmi (Tri-ponderal Mass Index)unclassified